Characterization of three Himalayan rocks using a split Hopkinson pressure bar. (May 2016) - Chakraborty, Tanusree; Mishra, Sunita; Loukus, Josh; Halonen, Brent; Bekkala, Brady
Highlights: Dynamic stress–strain response of quartzite, limestone and dolomite studied. 38 mm diameter split Hopkinson pressure bar (SHPB) device used. Physical and static mechanical properties properties determined. Dynamic peak stress, elastic modulus and force equilibrium studied. Correlation equations for DIF proposed.